Time Headway Modeling and Capacity Analysis of Pedestrian Facilities Involving Individuals with Disabilities. Issue 1 (2016) - Sharifi, Mohammad Sadra; Stuart, Daniel; Christensen, Keith; Chen, Anthony
Walking infrastructure should be designed to be effective for the needs of all pedestrian groups. Unfortunately, individuals with disabilities are often ignored in pedestrian facility analysis and design because of the lack of data on their walking behavior. A large-scale controlled walking experiment involving individuals with disabilities was conducted at Utah State University to observe individual pedestrian walking behavior on various walking facilities, including a passageway and a bottleneck. The purpose of this study was twofold: to model the time headway between individual types by using a mixed distribution model and to estimate passageway and bottleneck capacities and identify the impact of involving individuals with disabilities on capacity estimation. Analysis revealed that visually impaired individuals and individuals using nonmotorized wheelchairs and walkers caused the minimum capacity reduction on passageways and bottlenecks, whereas individuals using motorized wheelchairs caused the maximum capacity reduction in these areas. The findings are expected to improve the estimation of the facility capacity required to meet a preferred level of service for heterogeneous populations.